A mediation role of sustainable supply chain in e-procurement of ADNOC the largest energy company in UAE - AlQubaisi, Ahmed Jumaa Saeed Naser; Emran, Nurul Akmar; Mohd Sam, Mohd Fazli (ASR Research India, 2022)
Procurement practices remain one of the success factors in oil and gas industry. Weak procurement performance is the main reason for the delay in distribution, growth failures, and delivery of goods. Current strategies for constructing effective supply chains have shifted because of technological advancements. Indeed, corporations' enthusiasm for the use of the internet and information technology in the process of procurement motivates researchers to examine the impact of electronic procurement on the supply chain and overall procurement performance. In order to optimize the procurement process in oil and gas sector, Abu Dhabi National Oil Company (ADNOC) the largest energy company in United Arab Emirates (UAE) adopted e-procurement as the main way for bidding and solicitation of goods so that to achieve effective sustainable supply chain. However, it is still unclear to what extent e-procurement enhances the procurement of goods with the aid of supply chain. Based on this gap, the aim of this study is to examine the model fit of a conceptual framework that construct these three variables and testing the significance of correlations between e-procurement, sustainable supply chain, and procurement performance. The study employed a descriptive survey design and quantitative methodology. The employees working in tendering, procurement and evaluation committees, as well as the three-level of management, were purposively. Based on a sample of 376 questionnaires in ADNOC, we empirically investigate through using AMOS-SEM analysis. The result revealed that the three constructs (e-procurement, sustainable supply chain, and procurement performance) have significant and positive correlations. Based on this finding, it is highly recommended to focus on supply chain to foster the impact of e-procurement towards procurement performance of ADNOC. The outcome of this study provided an empirical evidence to the leaders in ADNOC and other oil and gas company that e-procurement is an essential success factor for sustainable supply chain and raising the effectiveness of procurement process, which in turn ensure swift delivery of energy products to consumers. Furthermore, the researcher anticipates that the findings and policy recommendations derived from this study will be of significant value to the oil company's stakeholders in general, both in the United Arab Emirates and throughout the world.